Al-Taṣnīf bayna ʿUlamāʾ al-Sawāḥil al-Sharqiyyah wa-Sumāṭrah al-Gharbiyyah: Dirāsah Muqāranah fī al-Bawāʿith wa-al-Ahdāf - Muhammad Sahni Arja (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
This paper examines the objectives and motivations behind scholarly classification and authorship among scholars of the eastern coastal regions and West Sumatra. The study reaches three main conclusions. First, not all scholars engaged in writing, nor did they share the same level of scholarly achievement, as shown through a comparative analysis of the two regions. Second, the intellectual climate of West Sumatra appears more vibrant, with a higher status of knowledge and learning. This does not suggest the absence of scholars in the eastern coastal areas, but rather that their number and scholarly output were not comparable to those in West Sumatra. Third, West Sumatra’s scholarly and intellectual centers significantly surpassed those of the eastern coasts. Scholars in the eastern regions tended to emphasize practical and behavioral Sufism, establishing numerous suluk-based institutions and lodges affiliated with Sufi orders, yet they did not develop systematic traditions of authorship to the same extent. Although Islam and Sufi orders entered both regions at roughly the same time through Sufi scholars, their trajectories diverged: the eastern coasts prioritized devotional practice, while West Sumatra combined spiritual discipline with sustained scholarly production.